Systematic Review: Pengaruh Berjalan Setelah Makan terhadap Glukosa Postprandial Penderita Diabetes Melitus Tipe 2 - Anggia Skynta Febrianty; Muhamad Faishal Ramadhan; Ieva B Akbar; Fajar Awalia Yulianto (Bandung Conference Series: Medical Science, 2022)
Abstract. Diabetes mellitus is a serious health problem, because it is expected to continue to increase in the next twenty years, and more than 70% of patients will appear in developing countries. Postprandial glucose has a major role in glycemic control. One of the important methods of treating type 2 diabetes mellitus (DMT2) is increasing physical activity. Walking is a physical activity that almost everyone can do. The purpose of this study was to assess the effect of walking after eating on the control of postprandial blood sugar levels in patients with T2DM. This study uses a method systematic review from the database Pubmed, Springerlink, Sciencedirect, and Proquest with keywords (Adult OR Aged) AND "Diabetes Mellitus, Type 2" AND (Walking OR "Walking Speed") AND "Blood Glucose" AND "Postprandial Period" AND "Randomized Controlled Trial" taken from 2011-2021 . Articles that meet the inclusion criteria are 133 articles, and those included in the exclusion criteria are 129 articles. The results of the feasibility test based on PICOS are 4 articles. After a critical review, there are 3 articles left. Measurement of articles using Continuous Glucose Monitoring System and Homeostasis Model Assessment-Insulin Resistance. The results showed that T2DM patients who walked after eating had lower postprandial blood sugar compared to the control group. Walking causes autophosphorylation of insulin receptor substrates so that the Phosphatidylinositol-3-kinase pathway is activated and then there is a transfer of Glucose transporter type 4 to the cell surface which increases the ability of target cells to take blood sugar efficiently and postprandial blood sugar levels in circulation will decrease. Abstrak. Diabetes melitus menjadi masalah kesehatan yang serius, karena diperkirakan akan terus meningkat dalam dua puluh tahun ke depan, dan lebih dari 70% pasien akan muncul di negara berkembang. Glukosa postprandial memiliki peran utama dalam kontrol glikemik. Salah satu metode penting pengobatan diabetes melitus tipe 2 (DMT2) adalah peningkatan aktivitas fisik. Berjalan merupakan aktivitas fisik yang dapat dilakukan oleh hampir semua orang. Tujuan penelitian ini untuk menilai pengaruh berjalan setelah makan terhadap pengendalian kadar gula darah postprandial pada penderita DMT2. Penelitian ini menggunakan metode systematic review dari database Pubmed, Springerlink, Sciencedirect, dan Proquest dengan kata kunci (Adult OR Aged) AND "Diabetes Mellitus, Type 2" AND (Walking OR "Walking Speed") AND "Blood Glucose" AND "Postprandial Period" AND “Randomized Controlled Trial” yang diambil dari tahun 2011-2021. Artikel yang sesuai dengan kriteria inklusi sebanyak 133 artikel, dan yang termasuk dalam kriteria eksklusi sebanyak 129 artikel. Hasil uji kelayakan berdasarkan PICOS sebanyak 4 artikel. Setelah dilakukan telaah kritis, tersisa 3 artikel. Pengukuran artikel menggunakan Continuous Glucose Monitoring System dan Homeostasis Model Assessment-Insulin Resistance. Hasil menunjukkan bahwa penderita DMT2 yang berjalan setelah makan, memiliki gula darah postprandial yang lebih rendah dibandingkan dengan kelompok kontrol. Berjalan menyebabkan autofosforilasi Insulin receptor substrates sehingga jalur Phosphatidylinositol-3-kinase teraktivasi lalu terjadi perpindahan Glucose transporter type 4 ke permukaan sel yang meningkatkan kemampuan sel target untuk mengambil gula darah secara efisien dan kadar gula darah postprandial di sirkulasi akan menurun.